(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Prison institutions are one of the three mainconstituents of the Criminal Justice System. With the changing perceptiontowards prisoners, prisons are no longer regarded as places for punishmentonly. They are now being considered as Reformatories and greater attention isbeing given to ameliorate the conditions in jails so that they have a healthyimpact on prisoners in developing a positive attitude towards life and society.A comprehensive database is being developed at the National level on allaspects of these institutions which will be of immense use to prisonauthorities in planning various activities connected with prisonadministration. The input forms have been reviewed and made more comprehensivein 2000 to collect data on every institution for the year 2007 is thethirteenth issue in the series.